2022
DOI: 10.3389/fimmu.2022.978851
|View full text |Cite
|
Sign up to set email alerts
|

MX2: Identification and systematic mechanistic analysis of a novel immune-related biomarker for systemic lupus erythematosus

Abstract: BackgroundSystemic lupus erythematosus (SLE) is an autoimmune disease that involves multiple organs. However, the current SLE-related biomarkers still lack sufficient sensitivity, specificity and predictive power for clinical application. Thus, it is significant to explore new immune-related biomarkers for SLE diagnosis and development.MethodsWe obtained seven SLE gene expression profile microarrays (GSE121239/11907/81622/65391/100163/45291/49454) from the GEO database. First, differentially expressed genes (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…This could explain why we found different predictors than previous studies. The number of studies using multiple algorithms to identify key genes or biomarkers is growing, and we believe that this will become a new trend (Meng et al 2022;Zhang et al 2022a). Actually, it remains challenging to identify predictors for disease outcomes in blood, and further laboratory and clinical researches are needed to validate our results.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why we found different predictors than previous studies. The number of studies using multiple algorithms to identify key genes or biomarkers is growing, and we believe that this will become a new trend (Meng et al 2022;Zhang et al 2022a). Actually, it remains challenging to identify predictors for disease outcomes in blood, and further laboratory and clinical researches are needed to validate our results.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, MX2 was found to be an immune-related biomarker for SLE, which can be used for predicting the diagnosis and disease activity of SLE. MX2 activates the NOD-like receptor signaling pathway, promotes neutrophil in ltration, and may worsen the condition of SLE [14]. Another study identi ed 28 hub genes, such as RPS7, RPL19, RPS17, and RPS19, playing important roles in the occurrence, development, and prognosis of SLE [15].…”
Section: Discussionmentioning
confidence: 99%
“…136 For extrarenal flares, 59 63 66 101 106 113 137-148 approximately half of the reports used genetic or genetic expression datasets. Novel biomarkers predicting SLE flares or increased disease activity include MX2 106 and M1 143 gene expression and a nine-protein combination (PHACTR2, GOT2, L-selectin, CMC4, MAP2K1, CMPK2, ECPAS, SRA1 and STAT2). 101 The AUC of the best models in these reports ranged from 0.70 to 0.99.…”
Section: Lupus Science and Medicinementioning
confidence: 99%